A study of pain threshold in diabetics with neuropathic foot lesions. Issue 10 (October 1986) - Le Quesne, P M; Fowler, C J
Abstract : Pain thresholds to a pinch stimulus were measured at eight sites on the dorsum of both feet from 17 diabetic patients. Sixteen feet had neuropathic ulcers and seven had Charcot arthropathy. Vibration perception thresholds, radial nerve action potentials, muscle action potentials of flexor digitorum brevis, autonomic cardiovascular reflexes and reflex sweat output were also measured. Pinch pain threshold was abnormal in 15 diabetic feet, 11 having one or more insensitive sites. There was a greater variability in threshold between sites tested in diabetic than control subjects.